Imaging of Articular and Extra-articular Sports Injuries of the Hip - Boric, Igor; Isaac, Amanda; Dalili, Danoob; Ouchinsky, Michel; De Maeseneer, Michel; Shahabpour, Maryam (Seminars in Musculoskeletal Radiology, 2019)
Sports-related articular and periarticular hip injuries are common in athletes. Knowledge of patient complaints and clinical findings are crucial for adequate interpretation of imaging examinations. However, asymptomatic athletes can present abnormal imaging findings, and clinical presentation of hip injuries may be nonspecific. Therefore, a thorough examination of the hip and surrounding soft tissue images is essential.This review describes the intra-articular pathologies encountered in sports activities including labrum or cartilage lesions, associated or not with femoroacetabular hip impingement syndromes, as well as ligament teres injuries, using magnetic resonance imaging (MRI) or computed tomography arthrography. Different causes of snapping hip syndrome (from intra- and extra-articular origins) are also discussed and illustrated. The extra-articular forms of hip impingement syndromes including ischiofemoral and subspine impingement are depicted with MRI and ultrasound. Diagnostic imaging of bone avulsions, greater trochanteric syndrome, athletic pubalgia, and myotendinous injuries is also described.
Keywords: magnetic resonance imaging; hip joint; sports injuries; extra-articular; impingement